THE MARKET FOR CORPORATE SECURITIES A PROGRESS REPORT - Shapiro, Eli (Journal of Finance, 1957)
S ummary A t the end of 1945 the corporate universe was characterized by a low level of capital assets relative to sales and a high degree of liquidity. The decade ending in 1955 was noteworthy for the high absolute level of investment in plant, equipment, and inventory. Corporations experienced no great financing difficulties in carrying out their expansion program; interest rates did not rise sharply during the period. The bulk of corporate investment was financed from internal sources of funds—retained profits and depreciation allowances—with internal sources more important in the first half of the ten‐year period. The relationship between internal and external financing was primarily dependent on cyclical variations in business activity. In periods of rising business activity short‐term borrowing and new security issues were utilized to supplement internal funds. In periods of declining economic activity long‐term financing through security issues was continued on a reduced scale and short‐term bank debt was reduced. Over the decade ending in 1955 there was an increasing trend toward long‐term securities issued to finance investment in plant, equipment, and inventories. All bonds outstanding for non‐financial corporations more than doubled from $23 billion at the end of 1945 to $54 billion at the end of 1955. There was some evidence to suggest that reduction in spreads between stock and bond yields encouraged stock financing in the latter years of the period. The most striking phenomenon in the long‐term debt market was the precipitous decline in the importance of individuals as holders of corporate bonds. In less than twenty years individuals' holdings of outstanding corporate bonds fell from two‐thirds to about one‐fifth. The largest holders of corporate bonds were life insurance companies who accounted for 50 per cent of all issues outstanding. Directly placed corporate securities—almost entirely bonds—accounted for about 40 per cent of gross security issues in the postwar decade. Life insurance companies held over 90 per cent of directly placed securities outstanding. In 1955 and particularly in 1956 growing tightness was evident in the capital market. The liquidity of corporations was worked down and the rate of increase in corporate internal sources of funds also fell. Capital outlays continued to rise. Accessibility to the capital market became critical to insure accomplishment of investment programs. Corporations entered the capital market on an enlarged scale at a time of continued high demands for funds from other sectors of the economy. The fall in liquidity of financial institutions plus the pursuit of a restrictive monetary policy by the central bank served to intensify the rise in yields and led to sharp increases in new financing costs and tightening of contract terms.